Neuro-didactic Dynamics Training Teachers from Neuro-pedagogy: Dinámica de formación neurodidáctica de docentes desde la neuropedagogía (2023)
Introduction: This article is about the possibility of neurodidactic training of teacher in the Primary Education Bachelor Degree, which directly effects the training of future teachers aimed at attention to the diversity. Methodology: To materialize this possibility, the Neuropedagogy subject of the optional and elective curriculum of the “E”, curriculum career is addressed in the neurodidactic training of this professional as a response to the specific needs of comprehensive teachers training. Several research methods are triangulated, included data analysis, participant scientific observation as fundamental techniques of the case study (situational). Results and discussion: The value of the neurodidactic training dynamics explained to provide the primary teacher with the necessary tools for attention to the diversity in the educational context of elementary education and the solutions on the professional problems in the various contexts of action, the proposal is introduced from the social technologies approach due to the repercussion and impact it has from a sociological and pedagogical point of view, from the the neurodidactic training dynamics of the primary teacher. Conclusions: Revealing changes are expressed that are achieved by introducing the dynamics of neuro-didactic training through the development of knowledge qualities, skills and values of the personality aimed at the attention of the socio-educational context.